Clinical features and prognosis of MPO-ANCA and anti-GBM double-seropositive patients - Hu, Xueling; Shen, Chanjuan; Meng, Ting; Ooi, Joshua D.; Eggenhuizen, Peter J.; Zhou, Ya-ou; Luo, Hui; Chen, Jin-biao; Lin, Wei; Gong, Yizi; Xiong, Qi; Xu, Jia; et al. (Frontiers in Immunology, 2022)
Several lines of evidence implicate that there are distinct differences between patients with myeloperoxidase-antineutrophil cytoplasmic antibody and anti-glomerular basement membrane antibody double-seropositive patients and single-positive patients.Hence, we conducted a retrospective study from a single center in China to analyze the clinical and pathological features,and prognosis of DPPs. 109 patients with MPO-ANCA-associated vasculitis,20 DPPs and 23 patients diagnosed with anti-GBM disease from a large center in China were included in this study.The ratio of patients with renal biopsy in three groups were 100%, 50% and 100%, respectively.Their clinical and pathological characteristics, and outcomes were analyzed. The intensity of immune deposits in the kidney at diagnosis was detected by immunofluorescence.Furthermore, multivariate Cox hazard model analysis was used to assess the clinical and histological predictors of end-stage renal disease and death for DPPs. In our study, we found that patients in the DPP group were older than the other two groups.The DPP group had a higher value of serum creatinine and lower estimated glomerular filtration rate compared with MPO-AAV patients. On the contrary, the DPP group had a lower serum creatinine compared with patients with anti-GBM group. The proportion of patients with cardiac system involvement in the DPP group was higher than anti-GBM patients. Cellular crescents could be generally observed in renal biopsy of DPPs and patients with anti-GBM glomerulonephritis. In addition, Bowman’s capsule rupture was more common in DPPs than MPO-AAV patients.MPO-AAV had a better renal and overall survival outcome than DPPs. There was no significant difference of renal and overall survival outcome between DPPs and patients with anti-GBM disease. The incidence of ESRD in DPPs was negatively associated with lymphocyte count and eGFR. Elevated serum creatinine was confirmed as a risk factor of both renal and patient survival in DPPs. In summary, compared with anti-GBM disease, DPPs tended to involve multi-organ damage rather than limited to the kidney. It is highlighted that serologic DPPs have a worse renal and patient prognosis than MPO-AAV.Moreover, we found that the risk factor of renal survival of DPPs includes low lymphocyte count, elevated serum creatinine and reduced eGFR, and serum creatinine can predict patient survival.